AN ANALYSIS HOW DO GDP PER CAPITA, EXPORTS, LIFE EXPECTANCY, AND TRADE AFFECT ECONOMIC GROWTH IN CHINA? - Rahmat Olii; Fauziyah Adzimatinur (LP2M Universitas Bina Bangsa, 2024)
Gross domestic product (GDP) serves as an important indicator of economic growth, which drives extensive research due to its significant impact on social and political stability. This study investigates the relationship between economic growth and GDP, alongside key factors such as GDP per capita, exports, life expectancy, and trade in China. Analysing annual time series data from 1965 to 2015, regression test methodology and the classical assumption method were used as analytical tools in this study. The findings show that GDP per capita, exports, and life expectancy did not show any significant positive impact on China's GDP growth. However, trade emerged as the only influential factor that contributed significantly to GDP growth, underscoring the importance of global market engagement for sustained economic progress. GDP per capita measures the total value of a country's production divided by its population, while exports show goods and services sold abroad. Life expectancy estimates the average age of life at birth, and trade includes international buying and selling activity. This research offers valuable insights for policymakers and stakeholders, helping to understand and advocate for sustainable economic development in China and other countries